Theoretical Evaluation of Resonator Fiber Optic Gyroscope Composed of a Polarization-Maintaining and Single Mode fiber with Digital Phase Modulation Technique - Bobbili, Prasada Rao; Nayak, Jagannath; Pinnoji, Prerana Dabral; Rama Koti reddy, DV (International Journal of Computer Sciences and Engineering, 2015)
Resonator fiber optic gyroscope (RFOG) based on the Sagnac effect has the potential to achieve the inertial navigation system condition with a short sensing coil. RFOG based on fiber coupled semiconductor DFB-LD with an FPGA-based digital processor is set up. We evaluate the frequency drift due to the various non-reciprocal noise sources –shot-noise; backscattering, Shupe, Kerr effect and Faraday noises are calculated theoretically with single mode fiber (corning SMF-28)as sensor coil and compared with PM fiber( HB 1500G) as sensing coil with similar parameters. Bias of the gyro which is caused by the noise source is also analysed.